2013
DOI: 10.1016/j.bej.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Combined process for 2,4-Dichlorophenoxyacetic acid treatment—Coupling of an electrochemical system with a biological treatment

Abstract: A coupled process was studied for the removal of a chlorinated pesticide: 2,4-Dichlorophenoxyacetic acid (2,4-D). A home-made electrochemical flow cell was used for the pre-treatment and a biological treatment was then carried out using activated sludge supplied by a local wastewater treatment plant. 2,4-D was used as a target compound for the study. Several parameters were monitored during the biological treatment, like Dissolved Organic Carbon (DOC), the target compound and the major by-product. Pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 39 publications
5
49
0
6
Order By: Relevance
“…In recent years, the combined processes, in particular physicochemical and biological combined treatments, have received a growing attention for their efficiency to achieve complete mineralization of biorecalcitrant compounds with the objective to reduce operating costs [1][2][3][4][5][6][7][8][9][10][11][12]. In such systems, a physicochemical pretreatment such as an advanced oxidation process (AOP) or an electrochemical method is used to change the structure of pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the combined processes, in particular physicochemical and biological combined treatments, have received a growing attention for their efficiency to achieve complete mineralization of biorecalcitrant compounds with the objective to reduce operating costs [1][2][3][4][5][6][7][8][9][10][11][12]. In such systems, a physicochemical pretreatment such as an advanced oxidation process (AOP) or an electrochemical method is used to change the structure of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the use of these methods to achieve the pretreatment of recalcitrant pollutants have been carried out. They have shown their efficiency for the removal of several recalcitrant molecules such as phosmet an organophosphorous insecticide [14], a chlorinated phenoxy herbicide 2,4-dichlorophenoxyacetic acid [6,9,13] and extensively used antibiotics such as sulfamethazine [19] and tetracycline [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several physicochemical methods have been proposed for their degradation [1][2][3][4][5][6]. Among them, the catalytic reduction of chlorinated compounds has been the subject of numerous investigations because of its high importance both for synthetic chemistry and environment [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these authors the main aromatic intermediate found was 2,4-dichlorophenol and oxalic acid as carboxylic acid. The 2,4-D degradation pathway also has been reported by Fontmorin [33,44] with electrolysis using bare graphite felt as anode. The results showed that chlorohydroquinone and 4-chlorocatechol were the most important intermediates found and 2,4-dichlorophenol and glycolic acid were also detected.…”
Section: Resultsmentioning
confidence: 83%